1995
DOI: 10.1113/jphysiol.1995.sp020647
|View full text |Cite
|
Sign up to set email alerts
|

The delayed basolateral membrane hyperpolarization of the bovine retinal pigment epithelium: mechanism of generation.

Abstract: three distinct phases. The first phase was generated by an apical membrane hyperpolarization, followed by a (delayed) basolateral membrane hyperpolarization (DBMH); the third phase was an apical membrane depolarization. The present experiments focus on the membrane and cellular mechanisms that generate phase 2 of the response, the DBMH.3. The DBMH was abolished in the presence of apical bumetanide (100 fM); this response was completely restored after bumetanide removal. Reducing apical [K+]O, adding apical bum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
(60 reference statements)
2
20
0
Order By: Relevance
“…Ammar et al, 1998;Hernandez et al, 1995;Hu et al, 1994Hu et al, , 1996, which under appropriate conditions fall within the range of 300e1600 U cm 2 depending on species and preparation (e.g. Arndt et al, 2001;Bialek et al, 1995;Blaug et al, 2003;Gallemore et al, 1993;Joseph and Miller, 1991;Kuntz et al, 1994;Peterson et al, 1997) characterized by freshly isolated tissues using combined Ussing chamber and microelectrode recording techniques. Recently improved cell culture techniques from human fetal cells resulted in RPE monolayers with transepithelial resistances between 500 and 800 U cm 2 (Hu and Bok, 2010;Maminishkis et al, 2006).…”
Section: Ussing Chamber Recordingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ammar et al, 1998;Hernandez et al, 1995;Hu et al, 1994Hu et al, , 1996, which under appropriate conditions fall within the range of 300e1600 U cm 2 depending on species and preparation (e.g. Arndt et al, 2001;Bialek et al, 1995;Blaug et al, 2003;Gallemore et al, 1993;Joseph and Miller, 1991;Kuntz et al, 1994;Peterson et al, 1997) characterized by freshly isolated tissues using combined Ussing chamber and microelectrode recording techniques. Recently improved cell culture techniques from human fetal cells resulted in RPE monolayers with transepithelial resistances between 500 and 800 U cm 2 (Hu and Bok, 2010;Maminishkis et al, 2006).…”
Section: Ussing Chamber Recordingsmentioning
confidence: 98%
“…The transepithelial transport of ions across the RPE begins with the activity of the apically localized Na þ /K þ -ATPase, which extrudes Na þ from the intracellular space of the RPE in exchange for K þ transportation into the RPE cytosol (Bialek et al, 1995;Blaug et al, 2003;Gallemore et al, 1993;Joseph and Miller, 1991;Miller and Edelman, 1990;Peterson et al, 1997;Steinberg, 1985). The resulting gradient for Na þ is used to take up Cl À , together with K þ , ions from the subretinal space via the activity of the Na þ /2Cl À /K þ -co-transporter (Arrindell et al, 1992;Bialek et al, 1995;Crewther et al, 2008;Hu et al, 1996;Hughes et al, 1998;Joseph and Miller, 1991;Miller et al, 1982). The influx of K þ into the RPE cytosol is counterbalanced by an efflux of K þ across the apical membrane back into the subretinal space (Fig.…”
Section: Inward-rectifier K þ Channelsmentioning
confidence: 99%
“…The slow light peak of the EOG is produced by the liberation of an unknown substance from the retina, which has been shown to affect second-messenger systems in the apical membrane of the RPE. The rapid initial light ''trough'' of the FO is generated by a light-evoked decrease in chloride ion (Cl -) concentration within RPE cells with subsequent hyperpolarization of the basolateral RPE membrane [19,20]. Two proteins within the RPE membranes in particular, the Cl-channel and cystic fibrosis trans-membrane conductance regulator (CFTR), have been implicated in the FO [12].…”
mentioning
confidence: 99%
“…This was supported by other groups investigating chloride currents of RPE cells in the whole-cell configuration (Botchkin and Matthews 1993 ;Ueda and Steinberg, 1994). In the ERG, external application of DIDS reduced changes at the basolateral membrane of the RPE which were due to efflux of chloride out of the cell (Bialek and Miller, 1994 ;Bialek, Joseph and Miller, 1995). In studies using the ERG it has been concluded that externally applied DIDS acts on a basolateral chloride channel (Bialek and Miller, 1994 ;Bialek et al, 1995 ;Fujii et al, 1992).…”
Section: Discussionmentioning
confidence: 84%
“…In the ERG, external application of DIDS reduced changes at the basolateral membrane of the RPE which were due to efflux of chloride out of the cell (Bialek and Miller, 1994 ;Bialek, Joseph and Miller, 1995). In studies using the ERG it has been concluded that externally applied DIDS acts on a basolateral chloride channel (Bialek and Miller, 1994 ;Bialek et al, 1995 ;Fujii et al, 1992). At present we have no explanation for this discrepancy between ERG and patch-clamp studies.…”
Section: Discussionmentioning
confidence: 84%